Existence and prevalence of debt specialization strategy across organizations: A Pakistani perspective - Kanwal Iqbal Khan; Faisal Qadeer; Albert John; Muhammad Sheeraz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The focus of capital structure research has now been diverted towards understanding the discriminating features of different debt instruments and explaining why to select a specific type of debt among different options? When companies predominantly borrow from fewer debt types, it is regarded as debt specialization (DS). The existence of DS has been empirically confirmed in some of the developed countries. But, researchers are far from reaching a conclusion that DS is a global phenomenon. Therefore, this paper is aimed to extend the canvas of DS debate by proffering new evidences for the existence and relevance of DS strategy among different organizational grouping. We use panel data for 410 non-financial publically traded companies of Karachi Stock Exchange from 2009 to 2013. The results of cluster analysis, threshold and conditional debt structure has confirmed the presence of DS. Our empirical findings indicate that 67% of the organizations exclusively rely on a single type of debt. The short term debts dominate in the debt structure of Pakistani companies, followed by secured and other long term debts. Additionally, through a comparative analysis among various organizational grouping based on profitability, age, credit rating, size, leverage, growth, dividend payments, regulations and business group affiliation, we identified similar trends of DS prevailing in five of the nine selected grouping variables. The paper also suggests several implications and directions for future research.
Keywords: 330; debt specialization; capital structure; debt instruments; organizational grouping